The Relationship of Fetuin-A, Adiponectin, Retinol Binding Protein-4 (RBP-4) and High Sensitivity C-Reactive Protein (hsCRP) with Insulin Resistance (HOMA-IR) in Obese Non Diabetic Men - Imelda Novianti; Andi Wijaya; Marsetio Donosepoetro (The Indonesian Biomedical Journal, 2012)
BACKGROUND: Central obesity is the accumulation of visceral (intra-abdominal) fat and is strongly known to be associated with insulin resistance and type 2 diabetes mellitus (T2DM). Obesity can cause adipocyte hypertrophy that results in dysregulation of adipokine expression. The abnormal function of adipocytes may play an important role in the development of a chronic low-grade proinflammatory state associated with obesity. Adiponectin, retinol binding protein (RBP)-4 and fetuin-A play a role in the pathophysiology of insulin resistance. Expression of fetuin-A is increased due to fat accumulation in the liver. Elevated concentration of fetuin-A in the circulation can impair insulin signaling in muscle and liver as well as suppress adiponectin secretion, although its molecular mechanism is still unclear. The aim of this study was to identify the relationship of fetuin-A, adiponectin, RBP-4 and hsCRP with insulin resistance in obese non diabetic men.METHODS: This was an observational study with a cross-sectional design. The study subjects were 64 men with non diabetic abdominal obesity, characterized by waist circumference of 98.47 ± 5.88 cm and fasting blood glucose of 85.75±8.36 mg/dL.RESULTS: This study showed that fetuin-A was positively correlated with HOMA-IR in obese non diabetic men with insulin resistance (r = 0.128; p = 0.570), although not significant. Fetuin-A was found to be correlated with adiponectin, RBP-4 and hsCRP (r=0.150; p=0.233; r=0.050; p=0.711; r=-0.04; p=0.445), although not significant.CONCLUSIONS: The concentration of fetuin-A showed a tendency to be positively correlated with HOMA-IR and with RBP-4 in obese non diabetic men, although statistically not significant. The concentration of fetuin-A showed a tendency to be negatively correlated with adiponectin and hsCRP although statistically not significant. There was no interrelationship between fetuin-A, adiponectin, RBP-4, hsCRP and HOMA-IR. Elevated concentrations of fetuin-A were noted in obese subjects, which in turn might impair insulin signaling. This finding might suggest that fetuin-A may represent a new target for the prevention of insulin resistance. Further studies might be needed on obese population with fatty liver.KEYWORDS: fetuin-A, adiponectin, RBP-4, hsCRP, insulin resistance